Validação de um método de laboratório alternativo à estimativa da capacidade de campo in situ - Chaves, Arilene Franklin (2017)
The knowledge of soil moisture in field capacity is determinant for rational and efficient irrigation programs. The estimation of the in situ field capacity moisture by the instant profile procedure is costly, operationally laborious and takes time to obtain the results. It is usual to estimate the soil moisture corresponding to the field capacity by laboratory procedures, operationally faster, and the Richards extractor method is the most used. The inconvenience observed in this procedure is the presumption that the water, at the field capacity, is under fixed maximum potential, independent of soil characteristics. An alternative procedure, performed in a laboratory, was presented by Ribeiro (2000), called a wet bulb, in which the search for the soil-water equilibrium condition is done by adding a small amount of water to the soil sample, without the fixation of Potential. The hypothesis of the work is that the energy (and hence quantitative) equilibrium of the soil-water relationship occurs in a similar way, whether the procedure is started with saturated soil or with any other amount of water; which occurs in less time when the initial amount of water is less than that of saturation and that at a given time, the amount of water in equilibrium is equal to that obtained in the field procedure. Thus, the objective was to estimate the soil moisture in the field capacity using the field and wet bulb methods, to compare the results and to verify if there is a common time in which the equality of the estimates by the two procedures occurs, for any soil texture. In situ moisture was estimated by the instant profile procedure. In the laboratory, the wet bulb method was performed with two volumes and four times of redistribution of water, in five textural classes. The data were analyzed considering the completely randomized design, in a 2 x 4 x 5 factorial scheme with a control treatment (in situ). The data were normal and the F test was applied for analysis of variance. The means were compared by the Dunnett test at 5% significance. It was concluded that in the wet bulb method, the use of the 1 and 2 mL volumes with a time of 10 minutes for water redistribution replaces the in situ procedure in the textural classes analyzed.